Factors That Influence the Growth and Development Disorder for Children aged 1 - 5 years in the Liquica Internal Health Centre, Liquica Municipality, Timor-Leste, 2022 - Manuela Alves, Maria; de Jesus Amaral, Isabel; Noronha, Herminio; de Jesus, Acacio; da Silva Belo, Ostelino; de Fatima dos Santos Atya , Maria (CV RIFAINSTITUT, 2023)
Growth and development of children at the aged 1-5 is an action that requires maximum attention. Because at the age 1-5 it refers to a faster and most critical phase of child development, usually known as the golden money phase. This phase is esensial, because form the privasity and characteristic beginning from this, WHO (2014). rowth and development disputes are a serious problem for both developed and advance countries around the world, and growth is assessed by body weight, height, and head cycle, development is assessed by motor, social, emotional, speech and cognitive capacity. According to the World Health Organization (2020) it was discovered that 149 million children suffered stunting, 45 million children were weaker/seriously wasted and over 38 million obesity/weighted. On the other hand, the WHO also stated that child mortality in the age of < 5 increased by 45% due to lack of nutrition. According to data by the Ministry of Health of Timor-Leste, (2018) children aged 1-5 years of age suffering from malnutrition were 1.521, men 734 and women 787. In this research, quantitative discretive aproach cross sectional Type of saturate sampling has a total of 29 people. Data collection techniques are used by a questionary with questions closed. To know the factors that influence the growth and development disturbances of children aged 1-5 years old at the Liquica Internal Health Centre, Liquica Municipality. Based on the results of 29 respondents, the majority of child nutrition factors were 15 people (51.7%), the majority of child stimulations were 14 people (48.3%) and the majority of child growth and development disabilities were 15 people (51.7%). Statistics test using Spearman Rank Corelation nutrition for children with growth and development disabilities with the value of P-Value = 0.001 with the value of r = 0.573 * * and the correlation test of the factors of stimulation and growth and development disabilities with the value of P-Value = 0.003 with the value of r = 0.527*, resulting in evidence that the correlation is sufficiently strong.